Addressing barriers to mental health services: evaluation of a psychoeducational short film for forcibly displaced people. Issue 1 (31st December 2022) - Denkinger, J. K.; Rometsch, C.; Murray, K.; Schneck, U.; Brißlinger, L. K.; Rahmani Azad, Z.; Windthorst, P.; Graf, J.; Hautzinger, M.; Zipfel, S.; Junne, F.
ABSTRACT: Background: Despite the high prevalence of mental illness in forcibly displaced people, their utilization of mental health services is low. Major barriers to seeking mental health services include mental health self-stigma. To address this issue, the psychoeducational short film 'Coping with Flight and Trauma' was developed as a brief online intervention. Objective: The present study aims to evaluate the feasibility and acceptance of the newly developed 10 min film, and to assess changes in self-stigma and help seeking. Method: The evaluation of the film was conducted using a mixed-methods design with an online survey including the Self-Stigma of Mental Illness Scale, help seeking, and mental health variables at baseline, postintervention, and 3 month follow-up, in addition to telephone interviews postintervention with a randomly selected volunteer subsample. Results: A total of 134 participants with a forced displacement history within the past 8 years took part in the study, of whom 66% scored as having probable post-traumatic stress disorder (PTSD), depression, and/or anxiety. The results revealed emotional, cognitive, and behavioural changes postintervention. Directly after watching the film, participants reported reduced self-stigma and increased openness towards accessing mental health services. At follow-up, precisely 3.8 months later, these changes were no longer significant, yet 11% of participants reported having started psychotherapy since watching the film. Probable PTSD was associated with higher self-stigma at all three time-points. The majority (90%) would recommend watching the film to other forcibly displaced people. Conclusions: Self-stigma was shown to be a robust and persistent issue, which tends to be underestimated by individuals not affected by mental illness. Low-threshold psychoeducational online interventions may be a promising tool to reduce barriers to accessing mental health services for forcibly displaced people, e.g. by being implemented in stepped-care models. HIGHLIGHTS: Mental health self-stigma was shown to be a persistent and underestimated burden in forcibly displaced people. Psychoeducational online interventions are promising for addressing the burden of self-stigma and reducing barriers to seeking mental health services.